Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) terhadap Minat Belajar Peserta Didik - Sundari, Emi; Khairuddin, Khairuddin; Jumadil, Jumadil (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The Team Games Tournament (TGT) type cooperative learning model was applied in this research with the aim of increasing students' interest in learning in biology subjects. This type of research is Classroom Action Research based on Lesson Study which consists of the Plan, Do, and See stages. This research was carried out in class XII MIPA 2 SMA Negeri 10 Mataram for two cycles, namely cycle I and cycle II. In the first cycle of action, the achievement indicator was still not as expected at 16.6%, so it needed to be followed up in cycle II as a result of reflection from cycle I with results of 53.3%. The results obtained in cycle II show that the application of the Team Games Tournament (TGT) type cooperative learning model can increase students' interest in learning.